2013
DOI: 10.1073/pnas.1222724110
|View full text |Cite|
|
Sign up to set email alerts
|

Camouflage mismatch in seasonal coat color due to decreased snow duration

Abstract: Most examples of seasonal mismatches in phenology span multiple trophic levels, with timing of animal reproduction, hibernation, or migration becoming detached from peak food supply. The consequences of such mismatches are difficult to link to specific future climate change scenarios because the responses across trophic levels have complex underlying climate drivers often confounded by other stressors. In contrast, seasonal coat color polyphenism creating camouflage against snow is a direct and potentially sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
236
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(249 citation statements)
references
References 36 publications
12
236
1
Order By: Relevance
“…For example, reversibly plastic adaptations like torpor (23) and hibernation (24) have been shown to occur in response to frequent (i.e., daily or yearly) and predictable changes in environmental conditions. In some examples of reversible phenotypic changes, such as the seasonal change in coat coloration in temperate mammals, there is even evidence that the increasing unpredictability of relevant environmental parameters is currently exerting strong selection on natural populations (e.g., snow cover for snowshoe hares) (25). Another potential example of reversible plasticity is cognitive ability, particularly given its role in enabling behavioral flexibility (26).…”
Section: Discussionmentioning
confidence: 99%
“…For example, reversibly plastic adaptations like torpor (23) and hibernation (24) have been shown to occur in response to frequent (i.e., daily or yearly) and predictable changes in environmental conditions. In some examples of reversible phenotypic changes, such as the seasonal change in coat coloration in temperate mammals, there is even evidence that the increasing unpredictability of relevant environmental parameters is currently exerting strong selection on natural populations (e.g., snow cover for snowshoe hares) (25). Another potential example of reversible plasticity is cognitive ability, particularly given its role in enabling behavioral flexibility (26).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the ability to change color more slowly, over periods of hours, days, and even weeks and months is likely to be more common in nature, yet has received relatively little study. Comparatively slow color change for camouflage has been shown to occur in, for example, prawns (Keeble and Gamble, 1900), caterpillars (Grayson and Edmunds, 1989), crabs (Stevens et al, 2013), and fish (Clarke and Schluter, 2011), in addition to seasonal changes in mammals and birds in line with the presence and absence of snow cover in winter and summer, respectively (Mills et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that hares have limited plasticity in their rate of colour change in the spring, but not in the fall rate, and not in the date the change initiates in either season (Mills et al, 2013;Zimova et al, 2014). The populations examined in these studies are expected to become severely mismatched over time (Mills et al, 2013).…”
Section: Individual Plasticity and Adaptive Potentialmentioning
confidence: 99%
“…The populations examined in these studies are expected to become severely mismatched over time (Mills et al, 2013). For at least one population, Zimova et al (2014) observed large differences in completion dates for the colour change that matched differences in snow cover.…”
Section: Individual Plasticity and Adaptive Potentialmentioning
confidence: 99%
See 1 more Smart Citation